Money Demand and Regional Monetary Policy in the West African Economic and Monetary Union - Rother, Philipp (IMF Working Papers; Working Paper ;, 1998)
Regional monetary integration, financial liberalization, and the adoption of indirect policy instruments have changed the conditions for monetary policy in the West African Economic and Monetary Union (WAEMU). The stability of money demand has become a crucial element for monetary policy. This paper presents empirical money demand estimations for regional monetary aggregates and analyzes their stability and forecast performance. The estimations result in a stable relationship for narrow money (M1). Consequently, the region';s central bank, the BCEAO, can continue to conduct monetary policy in line with the fixed exchange rate system if it succeeds in maintaining financial stability.